Ladies of the German Cinema - Hardy, Jack (Grapevine Video, 2009)
Berlin, Germany, 1921. The new Weimar Republic was in the midst of a powerful creative renaissance that still affects the arts as we know them today. Then and now, the most celebrated medium of Weimar Germany's artistic revolution was its movies, and some of Germany's most loved and celebrated actresses were at the height of their popularity. Some of those names include Asta Nielsen, Lil Dagover, and the two ladies featured in these two German films from 1921: Pola Negri and Henny Porten. [www.grapevinevideo.com]